Are the neuromotor disabilities of bilirubin-induced neurologic dysfunction disorders related to the cerebellum and its connections?. Issue 1 (February 2015) - Watchko, Jon F.; Painter, Michael J.; Panigrahy, Ashok
Summary Investigators have hypothesized a range of subcortical neuropathology in the genesis of bilirubin-induced neurologic dysfunction (BIND). The current review builds on this speculation with a specific focus on the cerebellum and its connections in the development of the subtle neuromotor disabilities of BIND. The focus on the cerebellum derives from the following observations: (i) the cerebellum is vulnerable to bilirubin-induced injury; perhaps the most vulnerable region within the central nervous system; (ii) infants with cerebellar injury exhibit a neuromotor phenotype similar to BIND; and (iii) the cerebellum has extensive bidirectional circuitry projections to motor and non-motor regions of the brainstem and cerebral cortex that impact a variety of neurobehaviors. Future study using advanced magnetic resonance neuroimaging techniques have the potential to shed new insights into bilirubin's effect on neural network topology via both structural and functional brain connectivity measurements.